Penerapan akuntansi SAK EMKM dalam penyusunan laporan keuangan studi kasus pada usaha sayangan di Desa Kebakalan - Rif’atul Fitriyyah; As’adi As’adi; Hermi Sularsih (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The purpose of this research is to know whether the financial statements of the business of love are in accordance with the SAK EMKM and to find out the obstacles in making reports. Data collection methods that will be carried out by researchers are: (1) Interview (2) Observation (3). Documentation. The results of interviews, observations and documentation carried out on the love business show that the business owner keeps records and makes bookkeeping reports. However, the owner admits that keeping records and compiling simple accounting reports is in accordance with the needs of the business owner. Recording and preparation of bookkeeping reports are still not in accordance with the science of accounting, because the recording does not show the stages like those in the accounting cycle and recording can only be understood by the business owner himself. The records carried out by Usaha Sayangan also do not show accurate results, because they do not carry out routine records and finances are still mixed with personal finances. Keywords: Accounting implementation SAK EMKM, Financial statement preparation